Potential of soil amendments (Biochar and Gypsum) in increasing water use efficiency of Abelmoschus esculentus L. Moench - Batool, Aniqa; Taj, Samia; Rashid, Audil; Khalid, Azeem; Qadeer, Samia; Saleem, Aansa R.; Ghufran, Muhammad A. (Frontiers in Plant Science, 2015)
Water being an essential component for plant growth and development, its scarcity poses serious threat to crops around the world. Climate changes and global warming are increasing the temperature of earth hence becoming an ultimate cause of water scarcity. It is need of the day to use potential soil amendments that could increase the plants’ resistance under such situations. Biochar and gypsum were used in the present study to improve the water use efficiency and growth of Abelmoschus esculentus L. Moench (Lady’s Finger). A six weeks experiment was conducted under greenhouse conditions. Stress treatments were applied after thirty days of sowing. Plant height, leaf area, photosynthesis, transpiration rate, stomatal conductance and water use efficiency were determined weekly under stressed (60% field capacity) and non-stressed (100% field capacity) conditions. Stomatal conductance and transpiration rate decreased and reached near to zero in stressed plants. Stressed plants also showed resistance to water stress upto five weeks and gradually perished at sixth week. On the other hand, water use efficiency improved in stressed plants containing biochar and gypsum as compared to untreated plants. Biochar alone is a better strategy to promote plant growth and WUE specifically of Abelmoschus esculentus, compared to its application in combination with gypsum.